Functionalized Oxoindolin Hydrazine Carbothioamide Derivatives as Highly Potent Inhibitors of Nucleoside Triphosphate Diphosphohydrolases - Afzal, Saira; al-Rashida, Mariya; Hameed, Abdul; Pelletier, Julie; Sévigny, Jean; Iqbal, Jamshed (Frontiers in Pharmacology, 2020)
Ectonucleoside triphosphate diphosphohydrolases (NTPDases) are ectoenzymes that play an important role in the hydrolysis of nucleoside triphosphate and diphosphate to nucleoside monophosphate. NTPDase1, -2, -3 and -8 are the membrane bound members of this enzyme family that are responsible for regulating the levels of nucleotides in extracellular environment. However, the pathophysiological functions of these enzymes are not fully understood due to lack of potent and selective NTPDase inhibitors. Herein, a series of oxoindolin hydrazine carbothioamide derivatives is synthesized and screened for NTPDase inhibitory activity. Four compounds were identified as selective inhibitors of h-NTPDase1 having IC50 values in lower micromolar range, these include compounds 8b (IC50 = 0.29 ± 0.02 µM), 8e (IC50 = 0.15 ± 0.009 µM), 8f (IC50 = 0.24 ± 0.01 µM) and 8l (IC50 = 0.30 ± 0.03 µM). Similarly, compound 8k (IC50 = 0.16 ± 0.01 µM) was found to be a selective h-NTPDase2 inhibitor. In case of h-NTPDase3, most potent inhibitors were compounds 8c (IC50 = 0.19 ± 0.02 µM) and 8m (IC50 = 0.38 ± 0.03 µM). Since NTPDase3 has been reported to be associated with the regulation of insulin secretion, we evaluated our synthesized NTPDase3 inhibitors for their ability to stimulate insulin secretion in isolated mice islets. Promising results were obtained showing that compound 8m potently stimulated insulin secretion without affecting the NTPDase3 gene expression. Molecular docking studies of the most potent compounds were also carried out to rationalize binding site interactions. Hence, these compounds are useful tools to study the role of NTPDase3 in insulin secretion.